Lignin‐Incorporated Supramolecular Copolymerization Yielding g‐C3N4 Nanoarchitectures for Efficient Photocatalytic Hydrogen Evolution. Issue 2 (12th October 2020) - Zhao, Chengxiao; Ding, Chao; Han, Chenhui; Yang, Xiaofei; Xu, Jingsan
Abstract : Graphitic carbon nitride (g‐C3 N4 )‐based nanostructures are a fast‐growing family of metal‐free semiconductors that have attracted much attention as hydrogen‐evolving photocatalysts. Previous research mostly uses small organic molecules to modify g‐C3 N4 for improved solar‐to‐fuel conversion efficiency; however, there are scarce reports on high‐efficiency g‐C3 N4 photocatalysts modified with natural macromolecules. Herein, lignin‐modified g‐C3 N4 nanoarchitectures with an ultrathin layered topography are successfully synthesized. The biomass‐modified g‐C3 N4 photocatalyst obtained through this method delivers a hydrogen‐evolving rate of 2235 μmol g −1 h −1, which is 3.5 times higher than that of g‐C3 N4 calcined from the preorganized cyanuric acid–melamine supramolecular assemblies. On the basis of experimental evidences, the improved hydrogen evolution reaction (HER) performance is attributed to synergistic effects between the ultrathin few‐layer 2D nanostructure, extended visible light absorption, and ideal energy band configuration. The biomass‐activated g‐C3 N4 nanostructures prepared via this synthesis route prove suitable for use as cost‐effective and efficient photocatalysts for scalable solar hydrogen production. Abstract : Lignin is used to modify g‐C3 N4 for improving photocatalytic activity. The lignin‐modified g‐C3 N4 photocatalyst shows a hydrogen‐evolving rate of 2235 μmol g −1 h −1, which is 3.5‐fold of pristine g‐C3 N4 . The enhanced hydrogen evolution is attributed to the hybridization effects between the ultrathin few‐layer 2D nanostructure, extending visible light absorption, and optimizing energy band configuration.